2004
DOI: 10.1007/s00404-003-0596-4
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation inhibitors in preeclamptic pregnant women

Abstract: The markers of hemostasis activation such as protein S, protein C activity together with fibrinogen levels are not useful tools but the reduction of AT-III and platelet counts would seem useful in different pathological situations in pregnancy to predict and monitor the severity of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
2
16
0
3
Order By: Relevance
“…We found that the PC activity of preeclamptic pregnant women was lower than that of healthy pregnant and non‐pregnant women. In contrast, there were no significant differences between the PC activities of the preeclamptic and healthy pregnant groups in two studies 18,19. …”
Section: Discussionmentioning
confidence: 68%
“…We found that the PC activity of preeclamptic pregnant women was lower than that of healthy pregnant and non‐pregnant women. In contrast, there were no significant differences between the PC activities of the preeclamptic and healthy pregnant groups in two studies 18,19. …”
Section: Discussionmentioning
confidence: 68%
“…, 1999; Kobayashi et al. , 2001, 2002; Osmanagaoglu et al. , 2005) and some authors have suggested that the assessment of this parameter could assist in differentiating PE from other forms of gestational hypertension, in which AT is unchanged (De Boer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Normal pregnancy is characterized by an increased plasma concentration of protein Z [37], which has been proposed to be part of a compensatory mechanism for the increased concentration of factor X [37] and perhaps for the increased thrombin generation. Preeclampsia is associated with an exaggerated hypercoagulable state and excessive thrombin generation [1,25,38], as determined by higher maternal plasma concentrations of TAT complexes [25][26][27][28]39,40] and lower antithrombin III concentrations [41][42][43][44][45] than patients with normal pregnancies. Moreover, patients with PE who deliver preterm have a higher rate of thrombotic lesions in the decidua [9,20] and in the placental villi [23] than normotensive patients with indicated or spontaneous preterm delivery [20,23].…”
Section: Discussionmentioning
confidence: 99%